2022
DOI: 10.3390/bioengineering9100518
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Blow Spun PLA/Gelatin Nanofibers Containing Green Synthesized Silver Nanoparticles against Wound Infection-Causing Bacteria

Abstract: One of the main challenges in wound healing is the wound infection due to various causes, of which moisture is the most important reason. Owing to this fact, wound dressings that can collect wound moisture in addition to showing antibacterial properties have provided an important basis for wound healing research. In this study, gelatin and poly lactic acid (PLA) polymers were used in a wound dressing textile to provide gelation and structure strength properties, respectively. Meanwhile, silver nanoparticles (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 52 publications
4
8
0
Order By: Relevance
“…Our results demonstrated that no antibacterial activity was detected for both pure PLA and pure PLA/PEO nanofibers used as control materials, since the CFU/mL overlapped those of bacteria in the absence of any type of nanofibers (growth controls). These results, in line with those of literature papers [ 37 , 38 ], revealed no intrinsic antimicrobial action of PLA-based electrospun nanofibers against different pathogens.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Our results demonstrated that no antibacterial activity was detected for both pure PLA and pure PLA/PEO nanofibers used as control materials, since the CFU/mL overlapped those of bacteria in the absence of any type of nanofibers (growth controls). These results, in line with those of literature papers [ 37 , 38 ], revealed no intrinsic antimicrobial action of PLA-based electrospun nanofibers against different pathogens.…”
Section: Resultssupporting
confidence: 93%
“…Altogether, the excellent results obtained by assaying the antibacterial effect of the AgNPs-loaded nanofibers, are well in agreement with those of the available scientific literature [ 23 , 24 , 37 , 39 , 40 , 41 ]. Mahapatra A. et al (2012) prepared polyacrylonitrile/Ag nanofibers, Shi Q. et al (2011) synthetized nylon 6/Ag nanofibers and both revealed an antibacterial action of the enriched samples [ 23 , 24 ].…”
Section: Resultssupporting
confidence: 90%
“…12 Alinezhad Sardareh et al developed polylactide (PLA)/gelatin nanofibers containing silver nanoparticles using SBS for wound healing. 7 This method demonstrated that SBS is a suitable and economical alternative for the large-scale production of nanofibers of an equal diameter. Tomecka et al presented poly( l -lactic acid) (PLLA) and polyurethane (PU) nanofibrous mats fabricated using SBS for cardiac cell cultures.…”
Section: Introductionmentioning
confidence: 90%
“…2,4,5 In contrast, SBS is a promising alternative for producing nanofibers from polymer solutions through volatilization in a high-pressure gas with a much faster spinning rate (several or even tens of times) than ES and does not require high-voltage operation scenarios, is capable of achieving multi-jet spinning and is therefore more equipped for safe and rapid fiber deposition. 4,6,7 In situ deposition on wounds introduces new perspectives and advantages over conventionally preformed nanofiber mats/meshes and scaffolds, which not only avoid direct contact with a wound but also easily fit irregular defect surfaces, thereby providing a rapid hemostasis/healing effect and avoiding the risk of secondary injury. [8][9][10] Tien et al fabricated highly deacetylated chitosan (CS) nanofiber scaffolds using SBS for their potential use as skin substitutes.…”
Section: Introductionmentioning
confidence: 99%
“…23 Adding silver or honey adds antimicrobial properties. [24][25][26] One of its main limitations is the need for a secondary dressing for optimal coverage and possibility of allergic reactions. 23 Common examples of alginates include Kaltostat (ConvaTec, Princeton, NJ), Sorbsan (Bertek Pharmaceuticals), Restore Calcicare (Hollister), Tegagen HG (high gelling) and Tegagen HI (high integrity) (3M Health Care), and Comfeel Plus (Alginate-hydrocolloid dressing) (Coloplast).…”
Section: Alginatesmentioning
confidence: 99%